Antibacterial and cytotoxic activities of the sesquiterpene lactones cnicin and onopordopicrin - Bach, Sandra M. (2011)
The antimicrobial and cytotoxic activities of chloroform extracts from the weeds Centaurea tweediei and C. diffusa, and the main sesquiterpene lactones isolated from these species, onopordopicrin and cnicin, respectively, were assayed. Results show that the chloroform extracts from both Centaurea species possess antibacterial activities against a panel of Gram-positive and Gram-negative bacteria. Remarkable antibacterial activity against methicillin-resistant Staphylococcus aureus was also measured. Both the extracts and the purified sesquiterpene lactones show high cytotoxicity against human-derived macrophages. Despite this cytotoxicity, C. diffusa chloroform extract and cnicin are attractive candidates for evaluation as antibiotics in topical preparations against skin-associated pathogens.